Religious Moderation Literacy Index of PTKIN Students in Aceh: Analysis of Islamic Knowledge and Understanding - Marhamah, Marhamah; Rohana, Sy.; Putra, Rahmad Syah; Khatami, M.; Hamarita, Mela (Analisis: Jurnal Studi Keislaman, 2024)
Religion should be a guideline for life and a filter against deviations in society. However, currently there is a growing understanding that leads to excessive and extreme religious practices, which are contrary to the essence of religious teachings themselves. To overcome this, the Ministry of Religion issued a policy on Strengthening Religious Moderation in PTKIN, which aims to be a space for sowing, educating, mentoring, and strengthening the religious moderation movement in the campus environment. This study uses a Mixed Methods approach with a survey to compile the components of the Religious Moderation Literacy Index (ILMB) based on a study by the Ministry of Religion. The research sample consisted of 100 PTKIN students in Aceh selected purposively with a 10% margin of error. Data were collected through observation, interviews, and questionnaires, then analyzed inductively based on the theory of religious moderation literacy and Islamic values. The results showed that the religious moderation literacy index of PTKIN students in Aceh was 50.48, which is relatively low. The basic understanding value of 57.67 and advanced understanding of 37.97 indicate that understanding of religious moderation needs to be improved. The students' knowledge of religious moderation that is not yet optimal shows the need for synergy between stakeholders and the use of social media. Strengthening religious moderation literacy in Aceh requires a comprehensive approach, including the integration of Islamic values in education and the use of digital media.